How to Be a Gricean Russellian (Aporia, 2018)
According to many philosophers, many utterances of sentences contain unarticulated indexical expressions. In response to the problem of incompleteness, for instance, many Russellians hold that definite descriptions contain unarticulated indexical expressions which restrict the denotation of the description’s nominal. I argue that such unarticulated indexical expressions pose a problem for Griceans who wish to explain meaning in terms of speakers communicative intentions. Roughly, the problem is that if there are unarticulated indexical expressions, then speakers can’t rationally intend to have their audience entertain a single complete proposition by their utterance of a sentence.Following Buchanan (2010), I suggest that the only way for the Gricean to meet this problem is to argue that often restricted proposition-types (and not propositions) are the objects of speakers communicative intentions. In particular, I argue that restricted proposition-types should be understood as proposition-types restricted by speakers’ actcoordinating intentions. In uttering a sentence speakers intend their audience to entertain any token proposition of their communicatively intended proposition-type; furthermore, speakers intend that the proposition the audience entertains by means of their utterance disposes them to act in coordination with the speakers intended action.